2019
DOI: 10.1016/j.jogc.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Severe Maternal Morbidity in Canada: Temporal Trends and Regional Variations, 2003-2016

Abstract: Objective: This study sought to quantify temporal trends and provincial and territorial variations in severe maternal morbidity (SMM) in Canada. Methods: The study used data on all hospital deliveries in Canada (excluding Qu ebec) from 2003 to 2016 to examine temporal trends and from 2012 to 2016 to study regional variations. SMM was identified using diagnosis and intervention codes. Contrasts among periods and regions were quantified using rate ratios (RRs) and 95% confidence intervals (CIs). Temporal changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 35 publications
(25 reference statements)
1
57
2
1
Order By: Relevance
“…Surgical complications, embolism, shock, uterine rupture, severe hemorrhage, and other serious adverse obstetric outcomes (Dzakpasu et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical complications, embolism, shock, uterine rupture, severe hemorrhage, and other serious adverse obstetric outcomes (Dzakpasu et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Maternal outcomes included preeclampsia, placental abruption, placenta previa, antepartum hemorrhage, postpartum hemorrhage, oligohydramnios, polyhydramnios, gestational diabetes, sepsis and other infections, cardiovascular disorders, renal disorders, acute liver failure, severe maternal morbidity, blood transfusion, and intensive care unit admission. Severe maternal morbidity was a composite variable which included life‐threatening conditions such as shock and eclampsia (Dzakpasu et al, ). We also identified complications of labor and delivery, including cesarean delivery, breech presentation, instrumental delivery (forceps, vacuum), perineal laceration, premature rupture of membranes, precipitate labor, and other complications (failed induction of labor, abnormal forces of labor, obstructed labor, prolonged labor, retained placenta, umbilical cord complications).…”
Section: Methodsmentioning
confidence: 99%
“…A recent review in New Zealand showed that at least onethird of SMM cases may be preventable, 29 and other studies have observed a high proportion of SMM due to obstetric haemorrhage. 13,17,30,31 It follows that the alleviation of anaemia in early-or mid-pregnancy might reduce both transfusion and SMMespecially those SMM elements more plausibly linked to a low haemoglobin ( Figure S1). In the present study, maternal adversity emerged at a haemoglobin concentration under 125 g/lconsiderably higher than the conventional level of 110 g/l recommended by others.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Severe maternal morbidity (SMM) offers a practical and validated proxy for maternal death (or 'near miss') and prolonged hospital length of stay, and it can be ascertained using population-based healthcare administrative data. [12][13][14][15][16] The SMM composite comprises about 40 morbidity measures arising in pregnancy, during labour or postpartum, 17 with an exponential rise in mortality as the number of SMM indicators increases. 13 If early pregnancy maternal haemoglobin concentration can identify women at risk for SMM later in pregnancy, this might naturally promote studies of interventions to reduce risk of SMM.…”
Section: Introductionmentioning
confidence: 99%
“…1 While maternal mortality has decreased in the developed world over the past 25 years, 2 a recent nationwide cohort study found that severe maternal morbidity (SMM) in Canada may be increasing. 3,4 The latest rate of SMM in Canada is around 17 cases per 1000 deliveries. 3…”
Section: Introductionmentioning
confidence: 99%